Stromal desmoplasia as a possible prognostic indicator in different grades of oral squamous cell carcinoma - Zainab, Heena (J Oral Maxillofac Pathol, 2019)
INTRODUCTION: One of the major aspects of tumor cell invasion and metastasis is the interaction between cancer cells and the extracellular matrix component. The invasion of epithelial tumor cells into the underlying connective tissue stroma causes dynamic changes in its microenvironment, which can be seen as radical changes in the stroma. The characteristics of the stroma in relation to the invading malignant epithelial cells and the interdependence between the stroma and the tumor cells are always a matter of discussion and interest. AIM: The aim of this study is to predict the biological behavior of oral squamous cell carcinoma (OSCC) by evaluating stromal desmoplasia and its possible use as important prognostic indicators. OBJECTIVE: To assess the desmoplastic reaction in varying histopathological grades of OSCC. MATERIALS AND METHODS: The study included a total of 30 histopathologically prediagnosed cases of OSCC (well, moderate and poorly differentiated grades of OSCC). Picrosirius red stain in conjunction with polarizing microscope was used to evaluate the stromal desmoplastic reaction. RESULTS: The results of the study revealed that, in the initial grades, cancer invasion induces a desmoplastic reaction, whereas in the later stages, there is degradation of the stroma, thereby facilitating tumor invasion. CONCLUSION: The study would emphasize the importance of stromal desmoplasia as a prognostic indicator and may help to reflect the biological diversity of oral cancer and predict the clinical outcomes.